Dampak Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Kasus Pada Pelanggan Dealer Yamaha Genuine Di Lowokwaru Kota Malang) - Fauzan Fauzan; Nur Hidayati; M. Ridwan Basalama (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research was conducted with the aim. 1) To determine and analyze the impact of price on customer satisfaction. 2) To determine and analyze the impact of service quality on customer satisfaction. 3) To determine and analyze the impact of price and service quality on customer satisfaction. The sampling method used was purposive sampling. The criteria that have been determined in this study are genuine Yamaha dealers in Lowokwaru, Malang city, lowokwaru sub-district people, aged 17 years and over, using and having bought a Yamaha motorcycle. Based on observations of these criteria, 55 respondents were obtained. Methods of data analysis using quantitative methods using test instruments testing, multiple linear analysis testing, classical assumption testing, f testing (simultaneous), t testing (partial testing), r square testing (coefficient of determination test), the results showed that all price variables negative impact on customer satisfaction, service quality has a positive impact on customer satisfaction, therefore price and service quality have a positive impact together on customer satisfaction. Keywords: Price, Service Quality, Customer Satisfaction